An extensive comparison between CBSEM and consistent PLS-SEM on producing the estimates of construct correlation in applied research - Wan Mohamad Asyraf, Wan Afthanorhan; Zainudin, Awang; Aimran, N.; Arifin, J. (2021)
Structural Equation Modelling (SEM) is always recognized as the method of choice across research fields when involving multiple construct, observed variables and relationships. However, there are a very few studies had investigated the SEM efficiency on producing the construct correlation. Thus, the Monte Carlo simulation was conducted on two different methods (CBSEM and Consistent PLS) using different sample size and model. The findings revealed that the CBSEM is performed consistently than Consistent PLS when the model being tested is in factor. The recommendations also provided to guide the SEM users.